Experimental Study on Physio-Mechanical Properties of Hybrid Teff Straw and Polyethylene Terephthalate Fibers Reinforced Concrete - Neway, Yeshitla (ASTU, 2023)
Concrete is one of the world’s most versatile and widely used construction materials. It is subject to many limitations in engineering applications because of poor ductility, high brittleness, low tensile strength, low tensile strain, and poor resistance to crack opening and propagation. Fiber hybridization with different types of fibers helps in resisting these cracks in concrete structures. Earlier studies have investigated the use of fibers in concrete structures to mitigate these weaknesses of plain concrete. However, the use of hybrid teff straw and polyethylene terephthalate fibers as hybrid reinforcing fibers in concrete has not been studied yet. In the current study, teff straw fiber was taken from harvested teff grain, and the polyethylene terephthalate fibers were extracted from plastic bottles to make hybrid fiber-reinforced concrete. To make hybrid teff straw and polyethylene terephthalate fiber reinforced concrete samples, ordinary Portland cement, fine aggregate, coarse aggregate, water, teff straw fiber, and polyethylene terephthalate fibers were directly mixed. The results of the slump and compaction factor values showed a reduction as the percentage of hybrid fibers increased compared to the control mix due to the interlocking of fibers and the incorporation of fibers absorbed more water from the concrete mix. At 28 days of cure, concrete mix with 0.2%, 0.4%, and 0.6% fibers concentration showed a compressive strength of 30.33Mpa, 21.72 MPa, and 19.21 MPa which is approximately 15.08%, 39.19%, and 46.21% lower than the control mix, respectively. This could be due to fiber balling effects and concrete becoming too hard to compact which in turn leads to more air voids thereby a decline in compressive strength. The investigation of splitting tensile and flexural strengths also revealed that the addition of 0.2% hybrid fiber concentration resulted in a 23.66% enhancement in splitting tensile strength and 7.84% enhancement in flexural strength, with the highest strengths of about 2.77 MPa and 5.09 MPa at 28-days, respectively. Failure mode during the test showed higher fiber concentration leads to a more ductile failure mode with fewer cracks than the brittle failure of control concrete, providing a sufficient warning before final failure. Furthermore, the current study revealed the enhanced tensile properties of concrete by incorporating teff straw and polyethylene terephthalate fibers.
Keywords: Hybrid fiber reinforced concrete; Teff straw fiber; Polyethylene terephthalate fiber; Crack; Fresh properties; Hardened properties